2014
DOI: 10.1007/s00417-014-2585-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of VEGF A and VEGFR2 polymorphisms in the response to intravitreal ranibizumab treatment for wet AMD

Abstract: Polymorphisms of VEGF A seem to influence the different response to antiangiogenic treatment in patients with AMD in our population, although further investigation is needed to know the mechanisms of this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…As Rap1b is implicated in promoting VEGF/VEGFR2-mediated angiogenesis, 15,16 which is important in neovascular AMD, 18,19 we restricted activation of Rap1 to only the Rap1a isoform by using Rap1b -/- mice. We previously published that activation of Rap1a with the chemical, 8-CPT-2Me-cAMP, delivered as an intravitreal injection, reduced CNV in Rap1b -/- mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Rap1b is implicated in promoting VEGF/VEGFR2-mediated angiogenesis, 15,16 which is important in neovascular AMD, 18,19 we restricted activation of Rap1 to only the Rap1a isoform by using Rap1b -/- mice. We previously published that activation of Rap1a with the chemical, 8-CPT-2Me-cAMP, delivered as an intravitreal injection, reduced CNV in Rap1b -/- mice.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Since the fold decrease in CNV volume in scAAV2-CARap1a versus scAAV2-Con was comparable to that from intravitreal anti-VEGF versus IgG, we wished to determine if activation of Rap1a affected VEGF expression or signaling. We previously found that laser-induced CNV increased NADPH oxidase-generated ROS in CNV 20 and VEGF protein in RPE/choroidal lysates in wild-type C57Bl/6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…This SNP was reported in three studies. 12 13 21 Although a significant association was reported only in one study, 16 for the recessive model, the effect of the genotype CC pointed to the same direction in studies of Cruz-Gonzalez et al 20 and Park et al 12 (OR=1.619 16 and OR=3.442, 12 with VA being the criterion), which strongly predicted a pooled OR=2.362 for the total analysis and the result was statistically significant (p=0.001), indicating that anti-VEGF treatment was more effective in patients with AMD having the rs833061 CC genotype. This relationship was strengthened further and became highly significant when a sub-analysis was conducted including studies with a VA-positive outcome criterion or the treatment of RBZ only, with OR=3.226 or OR=3.091, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results of each patient’s HER2, Erb2, and BRCA testing determine the chemotherapeutic regimens and surgical approaches. Single nucleotide polymorphisms (SNPs) from several genes—CFH, C2, C3, AMRS, HTRA1, hepatic lipase, VEGF, and VEGFR—are suspected to play a role in the development of advanced AMD but clinical studies cannot consistently predict patients’ responses to therapy based on genetic abnormalities [82,83,84,85]. Nonetheless, genetic studies continue with the hope that individualized therapy can someday be tailored to the presence or absence of AMD susceptibility genes.…”
Section: Present Datamentioning
confidence: 99%